Hospital performance standards and medical pricing: The impact of information disclosure in cardiac care. Issue 3 (19th June 2020) - Dor, Avi; Encinosa, William; Carey, Kathleen
Abstract: A policy concern is that the initiation of Hospital Compare (HC) reporting in Medicare provided leverage to insurers in price negotiations for lowering private sector prices without regard to hospital performance. Using the sequential Nash bargaining framework we provide economic intuition to the contrary: while average hospital prices decline under quality disclosures, hospitals with above‐average quality are able to exert a stronger bargaining position, consequently capturing prices above the market rate. To explore this issue empirically we estimate variants of difference‐in‐difference models, examining the effects of the three main scores (heart attack, heart failure, and combined mortalities) on transaction prices of related hospital procedures. States which had similar mandated reporting systems in place before the initiation of HC form the control group. Analyzing claims data of privately insured patients, we find that HC exerted downward pressure on prices. However, hospitals rated "above‐average" captured higher prices, thereby offsetting the overall policy effect fully or partially. Leads and lags analysis lends further support for our difference‐in‐difference approach. We find that highly ranked hospitals received a quality premium of 8–14%, comparable to price effects found in other health care markets. We conclude that HC was effective at constraining prices without penalizing high performers.